Canonizing Himself: Simon Dubnov's Book of Life and the Struggle for Hegemony in Jewish Historiography. Issue 1 (2nd January 2022) - Horowitz, Brian
ABSTRACT: Simon Dubnov is considered the father of Russian Jewish historiography without rivels or peers. An examination of his memoir shows that he intentionally fought with his colleagues and belittled their contributions. The author of this essays tries to answer why and how Dubnov did this.